2D Meso/Microporous Platelet Carbon Derived from Metal‐Organic frameworks and Its Application in High‐Performance Li‐S Batteries. Issue 12 (18th June 2019) - Qian, Weiwei; Zhang, Hang; Xiao, Hong; Zhang, Lan; Chen, Shimou; Gao, Qiuming
Abstract: A cathode consisting of 2D homogeneous micro/mesoporous platelet carbon (MMPC) is synthesized in one step by regulated pyrolysis of metal–organic frameworks (MOF), which act as self‐templates. The uniform micro/mesoporous structure is ascribed to metal sublimation in the Zn‐based MOF during the pyrolysis process. The cathode exhibits an excellent cycling performance due to the homogeneous distribution of micro/mesopores and the 2D nanosheet structure, which does not only lead to the loading of evenly distributed, ultrafine sulfur, but also favors the depressing shuttle effect and a rapid electron transfer. Meanwhile, reduced oxide graphene (rGO) – as the conductive agent – is beneficial for the continuity of the electron‐transport path and for increasing the utilization of active materials. The optimized MMPC cathode exhibits a superior cycling stability at a rate of 1 C, with 1500 cycles, and an outstanding rate‐cycle performance with an initial discharge capacity of 670.1 mAh g −1 and a good cycling stability after 400 cycles at a rate of 5 C. Abstract : A cathode consisting of 2D homogeneous micro/mesoporous platelet carbon is synthesized in one step by regulated pyrolysis of metal‐organic frameworks.